Transforming Growth Factor-Î²1 gene polymorphism and osteoporosis in postmenopausal egyptian women - Taha, Inass M.; Abdu Allah, Azza M.; Hamoudah, Maha A. F.; Justin Carlus, S. (Cellular and Molecular Biology, 2017)
Transforming growth factor-Î²1 (TGF-Î²1) is a wide spread bone matrix protein that affect the function, formation and cell-cell interactions of osteoclasts and osteoblasts to regulate bone remodeling and sustain adequate bone mass. The aim of this study is to evaluate the role of the two polymorphism of transforming growth factor-Î²1 T869C and C-509T in developing osteoporosis in postmenopausal Egyptian women. This study was performed on 138 postmenopausal osteoporosis/osteopenic women and 128 postmenopausal female control group. There was a significant statistical difference in the CC, CT and TT (T869C) genotype frequencies between the osteopenia/osteoporosis and control subjects (p value <0.001). There was a non-significant statistical difference in the CC, CT and TT (T-509C) genotype frequencies between the osteopenia/osteoporosis and control subjects (p value <0.082). There was a significant statistical difference between TT,CT and CC of (T869C) and T score, Z score and calcium of osteopenia/osteoporosis group (p value <0.001). There was a non-significant statistical difference between TT, CT and CC of (T-509C) and T score, Z score of osteopenia/osteoporosis group (p value 0.32,0.31),but there was a statistically significant difference between the three genotyping and serum calcium and creatinine (p value 0.04). Multivariate regression analysis showed that T869C polymorphism is a significant risk factor for osteopenia/ osteoporosis (OR 3.57, 95% CI= 1.56-5.67). We concluded that T869C polymorphism of the TGF-Î²1 gene has an impact on bone mineral density and enhancement of the susceptibility to osteopenia/osteoporosis in Egyptian women.